Atomistic simulations on the carbidisation processes in Pd nanoparticles. Issue 9 (14th February 2023) - Kordatos, Apostolos; Mohammed, Khaled; Vakili, Reza; Goguet, Alexandre; Manyar, Haresh; Gibson, Emma; Carravetta, Marina; Wells, Peter; Skylaris, Chris - Kriton
Abstract : The carbidisation mechanisms in PdC x nanoparticles are investigated through DFT. Insights on the preferential migration pathways from the surface to the interior are obtained towards the maximum interstitial C concentration. Abstract : The formation of interstitial PdC x nanoparticles (NPs) is investigated through DFT calculations. Insights on the mechanisms of carbidisation are obtained whilst the material's behaviour under conditions of increasing C-concentration is examined. Incorporation of C atoms in the Pd octahedral interstitial sites is occurring through the [111] facet with an activation energy barrier of 19.3–35.7 kJ mol −1 whilst migration through the [100] facet corresponds to higher activation energy barriers of 124.5–127.4 kJ mol −1 . Furthermore, interstitial-type diffusion shows that C will preferentially migrate and reside at the octahedral interstitial sites in the subsurface region with limited mobility towards the core of the NP. For low C-concentrations, migration from the surface into the interstitial sites of the NPs is thermodynamically favored, resulting in the formation of interstitial carbide. Carbidisation reaction energies are exothermic up to 11–14% of C-concentration and slightly vary depending on the shape of the structure. The reaction mechanisms turn to endothermic for higher concentration levels showing that C will preferentially reside on the surface making the interstitial carbide formation unfavorable. As experimentally observed, our simulations confirm that there is a maximum concentration of C in Pd carbide NPs opening the way for further computational investigations on the activity of Pd carbides in directed catalysis.